Validation of the SAFR-BE Tool: A Fire Index Assessment Method in Multi-storey Residential Buildings - Soraya,Farah (2025)
Nowadays, modern building design increasingly prioritized sustainability with Green Buildings concept is highly adopted. However, the potential increase of fire hazard in sustainable design remains a significant concern. To answer this challenge of the need for a method that integrate sustainable features with fire safety, the Sustainable and Fire Resilient Built Environment (SAFR-BE) tool was developed as a semi-quantitative index method that combines both fire safety and sustainable attributes. To ensure the consistency of SAFR-BE final index with another similar method, a validation study was performed using Quantitative Risk Assessment (QRA) through Event Tree Analysis (ETA). This validation study was also conducted to check whether SAFR-BE index is reliable to capture variations in results with the change to building layout scenarios. A fictitious building of multi-storey residential floor plan was used as a baseline, and a systematic parameters adjustment applied in both methods. The comparative study was carried out using six cases of the building layout, both open-plan and closed-plan floor plan with controlled adjustment of the parameter set both in QRA and SAFR-BE. The adjustment enables a direct comparison of how SAFR-BE final index changes with the QRA output under similar building conditions. From the comparative study, the study shows a strong alignment between the SAFR-BE and QRA results. The results show a consistent pattern, where the cases with the higher SAFR-BE index scores correspond to the lowest Individual Risk (IR) and Potential Loss of Life (PLL) values in QRA. This inverted pattern shows that when the SAFR-BE scores high, the building meets more favorable fire safety attributes. At the same cases, the QRA predicts reduced consequences and lower overall risk to occupants. These findings confirm that the SAFR-BE tool can reflect the risk identified through the quantitative analysis carried out because this is building as a study case.
Keywords: Fire index; Fire Assessment; Quantitative Risk Analysis; QRA; Validation Study; Semi-quantitative analysis